(untitled) (Journal of Hama University, 2024)
This study was aimed to detect Peste des Petits Ruminants disease (PPR) in sheep in Hama governorate. The study was involved 300 blood samples taken from infected sheep flocks of Peste des Petits Ruminants disease in Hama governorate. The serological results using competitive ELISA test showed 98/300 positive cases as total prevalence 32.67%. The higher prevalence of Peste des Petits Ruminants disease in sheep was reported in Alhamra area. As the prevalence was 60.00%, while some other areas like Taibat Alemam and Maards were not reported any positive cases. These results considered as indicator of severe condition on animal health and economic important impact.